The great Chinese inequality turnaround - Kanbur, Ravi; Wang, Yue; Zhang, Xiaobo (International Food Policy Research Institute, 2017)
The high level of inequality in China has been a focus of interest for policy makers and researchers. However, few studies have evaluated the trend since 2010. With changes in the economic structure and new policy tools introduced in recent years, a revisit of Chinese inequality should give us the latest information about its evolution and the impacts of these economic and policy changes on income distribution. This paper argues that after a quarter century of sharp and sustained increase, Chinese inequality is now plateauing and even turning down. The argument is made using a range of data sources and a range of measures and perspectives on inequality. The evolution of inequality is further examined through decomposition by income source and population subgroup. Some preliminary explanations are provided for these trends in terms of shifts in policy and the structural transformation of the Chinese economy. The narrative on Chinese inequality now needs to focus on the reasons for this great turnaround.